2018
DOI: 10.1039/c7cp06482a
|View full text |Cite
|
Sign up to set email alerts
|

Slow rheological mode in glycerol and glycerol–water mixtures

Abstract: Glycerol-water mixtures were studied at molar concentrations ranging from x gly = 1 (pure glycerol) to x gly = 0.3 using shear mechanical spectroscopy. We observed a low frequency mode in neat glycerol, similar to what is usually reported for monohydroxy alcohols. This mode has no dielectric counterpart and disappears with increased water concentration. We propose that the hydrogen-bonded network formed between glycerol molecules is responsible for the observed slow mode and that water acts as a plasticizer fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 62 publications
8
44
0
Order By: Relevance
“…This likely indicates that the water molecules have faster dynamics like in bulk water. The dynamical change of water molecules is likely coupled with aggregated water domains (Jensen et al, 2018). Furthermore, a negligible EISF means that water molecules are not restricted in confined space at the pico-second time scale.…”
Section: Resultsmentioning
confidence: 99%
“…This likely indicates that the water molecules have faster dynamics like in bulk water. The dynamical change of water molecules is likely coupled with aggregated water domains (Jensen et al, 2018). Furthermore, a negligible EISF means that water molecules are not restricted in confined space at the pico-second time scale.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, a constant temperature bath is utilized to raise the temperature to between 10 and 100 o C. More descriptions about the working principle and specifications of LVDV-2T Brookfield Viscometer are reported by Lahari et al [27]. [29] observed that "water acts as a lubricant, softening the hydrogen bonding which contributed to the macroscopic viscosity of the glycerol-water mixture". Takamura et al [30] observed that "the increase in viscosity of glycerol-water mixtures with the addition of glycerol is highly non-linear" and the variation in the aqueous phase was over three orders of magnitude.…”
Section: B Measurement Of Viscositymentioning
confidence: 99%
“…Fig. 7 Comparison of Viscosity of GW70 and SiO2 nanofluids Jensen et al[29] observed that "water acts as a lubricant, softening the hydrogen bonding which contributed to the macroscopic viscosity of the glycerol-water mixture". Takamura et al[30] observed that "the increase in viscosity of glycerol-water mixtures with the addition of glycerol is highly non-linear" and the variation in the aqueous phase was over three orders of magnitude.…”
mentioning
confidence: 99%
“…If one applies the model description of the preceding Section II to different glass formers, one learns many things. and of glycerol at 196 K [18]. The continuous lines are fits in terms of the model with the parameters given in Table I and II.…”
Section: A Overviewmentioning
confidence: 99%
“…This is illustrated in Fig. 1, which compares the normalized shear relaxation curves of the metallic glass Zr 65 Al 7.5 Cu 17.5 Ni 10 [17] with those of the hydrogen bonding molecular glass former glycerol [18].…”
Section: A Overviewmentioning
confidence: 99%